Time-Staged Gamma Knife Stereotactic Radiosurgery for Large Cerebral Arteriovenous Malformations: A Preliminary Report - Park, Hye Ran; Lee, Jae Meen; Kim, Jin Wook; Han, Jung-Ho; Chung, Hyun-Tai; Han, Moon Hee; Kim, Dong Gyu; Paek, Sun Ha (PLOS ONE, 2016)
Objective We retrospectively analyzed our experience with time-staged gamma knife stereotactic radiosurgery (GKS) in treating large arteriovenous malformation(AVM)s;≥ 10 cm3). Methods Forty-five patients who underwent time-staged GKS (2-stage, n = 37;3-stage,n = 8) between March 1998 and December 2011 were included. The mean volume treated was 20.42±6.29 cm3 (range, 10.20–38.50 cm3). Obliteration rates of AVMs and the associated complications after GKS were evaluated. Results Mean AVM volume (and median marginal dose) at each GKS session in the 37 patients who underwent 2-stage GKS was 19.67±6.08 cm3 (13 Gy) at session 1 and 6.97±6.92 cm3 (17 Gy) at session 2. The median interval period was 39 months. After follow-up period of 37 months, the complete obliteration rate was 64.9%. The mean AVM volume (and median marginal dose) at each GKS session in the 8 patients who underwent 3-stage GKS was 23.90±6.50 cm3 (12.25 Gy), 19.43±7.46 cm3 (13.5 Gy), 7.48±6.86 cm3 (15.5 Gy) at session 1, 2, and 3, respectively. The median interval duration between each GKS session was 37.5 and 38 months, respectively. After a median follow-up period of 47.5 months, 5 patients (62.5%) achieved complete obliteration. Postradiosurgical hemorrhage developed in 5 patients (11.1%) including one case of major bleeding and 4 cases of minor bleeding. No patient suffered from clinically symptomatic radiation necrosis following radiation. Conclusion Time-staged GKS could be an effective and safe treatment option in the management of large AVMs.